Exploring the radiation attenuation potential on waste eggshell-derived SiO2–CaO–B2O3–Na2O–P2O5–CaF2 bioactive glass for dental applications - Loh, Zhi Wei; Mohd Zaid, Mohd Hafiz; Matori, Khamirul Amin; Awang Kechik, Mohd Mustafa; Sa’at, Nor Kamilah; Kamal, Izdihar; Shah, Aishah Zarzali; Hisam, Rosdiyana; Cheong, Wei Mun (Springer Science and Business Media Deutschland GmbH, 2025)
This paper aims to study the radiation shielding potential of eggshell-derived bioactive glass with varying concentrations of calcium fluoride (CaF2) using the Phy-X simulation. Attenuation parameters such as the linear attenuation coefficient (µ), mass attenuation coefficient (μm), half-value layer (HVL), mean free path (MFP), effective atomic number (Zeff), exposure build-up factor (EBF), and energy absorption build-up factor (EABF) were evaluated across 0.015–15 MeV. The findings indicate that increasing CaF2 content enhanced the μm and µ from 2.164 cm2/g to 2.191 cm2/g and 4.600 cm−1 to 4.671 cm−1 at the energy of 15 MeV. At 662 keV, the HVL and MFP ranged between 0.0398–0.0406 cm and 0.0574–0.0586 cm, outperforming conventional concrete and commercial glasses like RS 360 and RS 253 G18 by 98–99%. Furthermore, the Zeff reaches a maximum of 15.463–16.046, while the EBF and EABF values drop with higher CaF2 concentrations. These findings demonstrate the significant impact of CaF₂ addition in improving the mechanical and radiation attenuation features of bioactive glass. Consequently, the synthesized bioactive glass compositions show great promise as alternative attenuation materials for medical and industrial applications requiring effective ionizing radiation protection.